Analisis Model Bauran Pemasaran terhadap Kinerja Pemasaran yang Berorientasi pada Keunggulan Bersaing Berkelanjutan di Supermarket X Surabaya - Minto Waluyo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Supermarket X is the retail business which offer and sell daily goods. Based on the field survey, there was the descent marketing performance at some department of supermarket X, thus it needs some strategies to increase the marketing performance.The model of measuring the performance uses the regression level, which means the Sructural Equation Modeling (SEM), as the tool. As a purpose indicating the the influential variables significantly and the uninfluential variables significantly Based on the conceptual framework, the model is not proper, thus it needs the modification model. The result of the modification model indicated that the mixed marketing influences the product significantly with the amount of -0,097. The mixed marketing influnces the price significantly with the amount of 0,197. The mixed marketing influences the distribution significantly with the amount of 0,226. The mixed marketing influence the promotion significantly with the amount of 0,038. The mixed marketing influnces the location significantly with the amount of 0,335. The mixed marketing influences the variation product sale significantly with the amount of 0,737. The mixed marketing influence the service department significantly with the amount of 0,375. The enterprice policies influences mixed marketing significantly with the amount of 0,601. The enterprice policies influenced the consumer attitude significantly with the amount of 0,320. The consumer’s attitude influenced the decision consumers significantly with the amount of 0,305. The consumer’s decision influenced the marketing performance significantly with the amount of 0,345 and the marketing performance influenced the superiority of ongoing competation significantly with the amount of 0,532.